MUDHARABAH DALAM FIQIH DAN PERBANKAN SYARI’AH (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
This research intends to know the theoretical foundations related mudharabah in jurisprudence and Shariah banking. The method used in this research is to study literature. The results showed that mudharabah is a contract between two parties whereby one party called rab al-mal (investors) entrusts money to the second party, called mudharib, for the purpose of running a trading business. Mudharabah contract has no basis in the Qur’an and Sunnah, the contract has been used to run a trade by the early generations of Muslims. Mudharabah contract is very different with the syariah bank mudharabah contract as generally described by maszhab-schools of fiqh, or as envisaged by the Shariah bank as a theoretical model of joint venture capital financing, or financing for industrial development.